Study of the Oxalate Ion Exchange Equilibria in Ion Exchange Resin Amberlite IRA-400 - B. PATIL, DILIP; P. GANORKAR, AJAY (Asian Journal of Chemistry, 2010)
The equilibrium constant in the standard state Kstd for the uni-bivalent ion exchange between the resin (R) and the aqueous solution (aq) where X- = Cl- or Br- have been determined in anion exchange resin Amberlite IRA-400 with regards to mean activity co-efficients of ions both in the solution and in the resin. The apparent equilibrium constant (kapp) for various equilibrium concentrations of C2O2–4 in the solution have been calculated from the expression. The equilibrium constant in the standard state (kstd) is determined by a graphical method. The resin in its purely univalent anion form is chosen as the standard state. From kstd for vairous temperatures, the enthalpy change for the ion exchange reaction has been evaluated.